Competitive Analysis and Business Strategies of NVOCCs in the Maritime Industry in Indonesia - Budi Nur Rochmadi; Prasadja Ricardianto; Librita Arifiani; Datep Purwa Saputra (Dinasti Publisher, 2026)
This study aims to explain the strategic adaptation mechanisms that shape the competitiveness of Non-Vessel Operating Common Carrier (NVOCC) companies in the competitive conditions of the Indonesian maritime industry. As providers of Less-than-Container-Load services, NVOCCs play an important role in integrating MSMEs into global trade and enhancing the efficiency of the national supply chain. However, NVOCCs face complex adaptive pressures arising from inter-institutional regulatory uncertainty, volatility in logistics costs, global market dominance, and accelerated digitalisation of logistics. This study uses a predominantly qualitative approach supported by secondary quantitative data. Data were collected through in-depth interviews, focus group discussions, and field observations at major Indonesian ports, as well as analysis of policy documents and industry reports. The analysis was conducted using NVivo and synthesised by integrating the PESTEL framework, Porter's Five Forces, the Resource-Based View, Porter's Generic Strategies, and the Herfindahl–Hirschman Index (HHI) as components shaping strategic adaptation mechanisms. The results show that NVOCC competitiveness is formed through dynamic and contextual strategic adaptation mechanisms. Regulatory and infrastructure instability trigger relational strategies and informal coordination, while cost pressures drive operational efficiency through cargo consolidation. Meanwhile, the dominance of global players and limited digital capabilities reinforces the need for technology-based service differentiation and customer relationships. An HHI value of 1,267 indicates a market structure with moderate concentration. Key findings confirm that adaptive hybrid strategies that combine cost efficiency and service differentiation are a key mechanism for maintaining NVOCC performance, particularly in the MSME export segment. This research contributes to the development of the Integrated Strategic Adaptation Model (ISAM) and provides implications for strengthening national logistics competitiveness.